2014
DOI: 10.1002/etc.2710
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for dissociation and photolysis: A review of the algal toxicity of triclosan

Abstract: Triclosan, an antimicrobial agent commonly used in down-the-drain consumer products, is toxic to freshwater microalgae. However, the rapid photolysis and pH-dependent dissociation of this compound may give rise to uncertainty in growth inhibition tests with freshwater microalgae, if these are not well characterized. Methods are presented to minimize these uncertainties by stabilizing pH with an organic buffering agent (Bis-Tris) and by the application of ultraviolet (UV) covers to remove UV wavelengths. Toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 36 publications
0
28
1
Order By: Relevance
“…The neutral form of TCS, at lower pH, has been reported to be more toxic than its ionized form (Rendal et al 2011 ). The effect of test media pH on TCS toxicity for microalgae has previously been reported for Scenedesmus subspicatus in which toxicity increases with decreasing pH until all TCS is present in an unionized state, then further decrease in pH has no influence as TCS becomes fully neutral at pH 6 and fully ionized at pH 10 (Roberts et al 2014 ). Therefore, there is still a need to investigate these effects for other algal species.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…The neutral form of TCS, at lower pH, has been reported to be more toxic than its ionized form (Rendal et al 2011 ). The effect of test media pH on TCS toxicity for microalgae has previously been reported for Scenedesmus subspicatus in which toxicity increases with decreasing pH until all TCS is present in an unionized state, then further decrease in pH has no influence as TCS becomes fully neutral at pH 6 and fully ionized at pH 10 (Roberts et al 2014 ). Therefore, there is still a need to investigate these effects for other algal species.…”
Section: Introductionmentioning
confidence: 89%
“…Two experiments were conducted in accordance with OECD guideline 201 (OECD 2006 ). One followed the guideline without modifications, but a second was conducted with two modifications adapted from the experiment of Roberts et al ( 2014 ), including (1) pH control using 4.5-mM Tris buffer at target pH level of 7.5 and (2) an acclimatization period of 2 × 72 h in the algal medium contained Tris buffer prior to the test. Tris buffer, or Tris(hydroxymethyl)methylamine, NH 2 C(CH 2 OH) 3 , ≥99.8 % Purity, was purchased from UNIVAR.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Brausch and Rand, 2011;Bedoux et al, 2012;Dann and Hontela, 2011;Hwang et al, 2014). It was found that TCS is highly toxic to algae (Roberts et al, 2014). For example, the 96 h growth inhibition EC 50 (median effective concentration) of TCS for Pseudokirchneriella subcapitata was 0.53 lg L À1 (Yang et al, 2008), which is even an order of magnitude below the aforecited maximum concentration of TCS in surface water.…”
Section: Introductionmentioning
confidence: 97%